2009
DOI: 10.2495/cp090191
|View full text |Cite
|
Sign up to set email alerts
|

Environmental impact assessment and HazOp study of the drilling cuttings confinement process into non-productive wells in marine platforms in Campeche, Mexico

Abstract: Potential risk and environmental impacts associated with the cuttings re-injection process as an alternative method for drilling wastes disposal were identified and assessed in two marine platforms facilities located in Campeche, Mexico. Environmental impacts were identified and assessed on physicochemical, biological-ecological, socio-cultural and economical elements using the Rapid Impact Assessment Matrix (RIAM). Drilling cuttings re-injection can cause negative effects with light changes. Most of negative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…A preliminary research performed by R.M, et al [76] simulated acid rain on coastal zone tree species that included white mangrove, red mangrove and button mangrove commonly found in Mexico. The authors suggested that low pH exposure will lead to stress development in mangrove trees.…”
Section: ) Acid Depositionmentioning
confidence: 99%
“…A preliminary research performed by R.M, et al [76] simulated acid rain on coastal zone tree species that included white mangrove, red mangrove and button mangrove commonly found in Mexico. The authors suggested that low pH exposure will lead to stress development in mangrove trees.…”
Section: ) Acid Depositionmentioning
confidence: 99%